Incorporating Data Citation in a Biomedical Repository: An Implementation Use Case - Gupta, Snehil (AMIA Jt Summits Transl Sci Proc, 2017)
Research data is a dynamic and evolving entity and the ability to cite such data depends on recreating the same datasets utilized in the original research. Despite the availability of several existing technologies, most data repositories lack the necessary setup to recreate a point-in-time snapshot of data, let alone long-term sustainability of dynamic data without restoring an entire database. Through this project, we adopted a subset of the Research Data Alliance data citation working group recommendations to establish a robust informatics system supporting dynamic data and its use for reproducible research within our evolving clinical data repository. We implemented key recommendations: data versioning, times-stamping, query storing, query time-stamping, query PID, and data citation in one data repository, implemented entirely at the database level, and were able to successfully reproduce a previous dataset as it existed at a specific point-in-time using only the PID as provided in a citation.